Using XML and flash to create a server-agnostic application XML is a key component in this ambitious project. - Blanchard, Scott
I recently undertook an extremely ambitious project in which I decided to convert an entire application user interface from Internet Explorer to the Flash-based .swf (pronounced "swift") format.